¨ Hemorragias de la primera mitad de la gestación asociadas a complicaciones obstétricas en pacientes Atendidas en el Hospital Iess Duran. octubre 2018 – abril 2019 ¨. - Mite Manzaba, Kevin Andrés (2019)
Obstetric hemorrhages have an incidence of three to five percent in pregnant women, therefore, they develop obstetric pathologies that are constantly associated with maternal and perinatal mortality. Worldwide, the annual figures determine that half a million women die during pregnancy or the part as a result of obstetric complications. The main objective of the present study was to determine hemorrhages of the first half of gestation associated with obstetric complications in patients treated at the IESS Duran Hospital. October 2018 - April 2019; A descriptive, observational and non-experimental study was conducted in 372 patients who were treated at the IESS Hospital in Duran, with the diagnosis of hemorrhage in the first half of pregnancy; In the results obtained from the survey, it is highlighted that the reason for attending the consultation of the respondents was that they had hypogastric pain, presenting as 75% the main factor of obstetric complications. Another complication was abortions with a 80%, Asherman síndrome with 43% and Infertility due to Ortectomy with 14% conclusion the purpose of this work is to know the main hemorrhages during the first half of pregnancy with their complications that come to the emergency service of the Basic Hospital IESS last during the period October 2018 April 2019 with the purpose of preventing maternal mobidity and mortality.